PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DALAM UPAYA MENEKAN KECELAKAAN KERJA DI PT. JASAMARGA BALI (TOLBALI MANDARA) - wijayanti, wayan (Jurnal Ilmiah Manajemen & Bisnis, 2016)
This study aimed to determine the application of Occupational Health and Safety Management System (SMK3) in an effort to suppress the rate of workplace accidents in PT. Jasamarga Bali Tol (Tol Bali Mandara). The Occupational Health and Safety Management System (SMK3) is part of the overall management system that includes organizational structure, planning, responsibility, implementation, procedures, processes and resources needed for the development, application, achievement, assessment and maintenance of safety and health policies in order to create a workplace that safe, secure, efficient and productive (Permen PU, 2008). This study used qualitative data derived from the documents in the company and also the Audit Checklist of Occupational Health and Safety Management System sourced from Minister of Manpower Regulation No.05 / MEN // 1996. Data analysis technique used was qualitative descriptive. The results of the data analysis obtained found a fact that this company in the application of SMK3 obtained Good category that got the Certificate and Golden Flag. It was achieved because the company had fulfilled the requirements of the Audit Check List as many as 146 elements (88%) of the 166 elements. The company was deemed to be in violation as many as 12% for 20 elements could not be fulfilled. For two years (2013-2015) there had been a nine cases of accidents suffered by the employees, it is suggested that in the future the company should continue to seek to complete the elements that are still violated in order to achieve all the elements determined by government regulation.